2014
DOI: 10.1111/1541-4337.12118
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Implications of Pasture‐Based Lamb Fattening to Enhance the Long‐Chain Fatty Acid Composition in Meat

Abstract: Health-conscious consumers following dietary fat recommendations require meat that is low in saturated fat with preferably high levels of long-chain omega-3 fatty acids. This review summarizes the influence of dietary lipids from red meat on human health and examines the potential to enhance lipid composition through pasture-feeding. The role of fatty acids in plant and ruminant metabolism is discussed to highlight the complexity of ruminal digestion when trying to enhance fatty acids in meat. Generally, rumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 179 publications
(309 reference statements)
6
70
0
3
Order By: Relevance
“…Similarly, Raes et al . and Howes et al . reported that linseed used as a feed ingredient in concentrate or grass‐based diets led to an increase in the muscle concentration of n‐3 PUFA in ruminants.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, Raes et al . and Howes et al . reported that linseed used as a feed ingredient in concentrate or grass‐based diets led to an increase in the muscle concentration of n‐3 PUFA in ruminants.…”
Section: Resultsmentioning
confidence: 87%
“…In ruminants, dietary PUFA undergoes biohydrogenation to SFA, which explains the inefficient deposition of PUFA in the muscle . However, the intermediates of ruminal biohydrogenation of C18:2n‐6 – rumenic acid, an isomer of conjugated linoleic acid (CLA c9,t11‐ C18:2), and trans‐vaccenic acid ( t11 ‐C18:1) – are of human health importance: t11 ‐C18:1 can either be converted to C18:0 through ruminal biohydrogenation or to CLA by the Δ 9 ‐desaturase enzyme . The effect of diet on the muscle proportion of CLA c9,t11‐ C18:2 indicated that BPR had a higher proportion than C ( P = 0.05; supplementary Table S1), which may be explained by the higher concentration of C18:2 in the BPR diet (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…(2006) and Howes, Bekhit, Burritt, and Campbell (2015) further explored nutritional strategies to enhance long chain PUFA in beef. Specifically, Scollan et al.…”
Section: Effects Of Farming Systems On Meat Qualitymentioning
confidence: 99%
“…Motivated by health‐conscious consumers, Howes et al. (2015) reviewed current literature to identify opportunities to enhance long chain PUFA in lamb fattening systems. Notably, the authors considered how specific cultivars of herbs and legumes might affect fatty acid profiles; Ådnøy et al.…”
Section: Effects Of Farming Systems On Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation